Multicriteria Decision Making Model For Faculty Member Selection - Mamat, Nur Jumaadzan Zaleha (2006)
The conventional process of selecting new faculty members requires great deals of evaluations and discussions by the selection committee. The implementation of a mathematically simple but comprehensive yet logical and structurally organized multi criteria decision making (MCDM) method will give a more scientific justifiable decision in the faculty member selection problem.